Business trends and opportunities: the emerging markets of religious foods - Haque, A. K. M. Ahasanul; Hashim, Nurhazirah; Ahmed, Faruk (Woodhead Publishing, Elsevier, 2018)
This chapter gives some forthcoming idea of marketable religious foods becoming increasingly demanding across the world. Particularly, noteworthy clarifications of the ideas of nourishment of wide range of religious food have been discussed. In addition, the relevance of religious foods in the market and the consumer's behavioral aim to consume religious food is the key talks in this chapter. Besides, the religious defense regarding nourishment has also been explained. The goal of this section is to help the consumer community pick religious nourishment s and, thus, it would enhance a sound way of life with adjusted eating regimen.